In vitro conservation of mangrove for pharmaceutical interest - Chinnappan Ravinder Singh (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2019)
Mangroves are halophytic species with unique morphological features, habituated in the intermediate zones of coastal area. They had better ecological community and serve as natural barriers. Since ancient times, mangrove forests are considered as the source of drugs, where tradition medicine and several healing practices were derived from the mangrove species. This potentiality was due the secretion of secondary metabolites to endure the extreme environmental conditions. In the recent years the utilization of mangroves was tremendously increased due to their variety of uses in industries and medicine. By this anthropogenic activity, severe loss and degradation of the mangrove forest area had been observed, which leads to negative ecological impact. To conserve these invaluable mangrove species, in vitro culture techniques was considered as the better practice. Our study reveals the impact of in vitro cultivation of mangroves and their necessity in the natural ecosystem.